Are Student Teachers’ Overall Expected Emotions Regarding Their Future Life as a Teacher Biased Toward Their Expected Peak Emotions? - Forster, Markus; Kuhbandner, Christof (Frontiers in Psychology, 2022)
Having functional expected emotions regarding one’s future life as a teacher is important for student teachers to maintain their motivation to choose a career as a teacher. However, humans show several biases when judging their emotional experiences. One famous bias is the so-called peak-end effect which describes the phenomenon that overall affective judgements do not reflect the average of the involved emotional experiences but the most intense and the most recent of the involved emotional experiences. Regarding student teachers’ expected positive emotions, such a bias would be functional since their motivation to become a teacher is enhanced. However, regarding student teachers’ expected negative emotions, such a bias would be dysfunctional since their motivation to become a teacher would be decreased. The aim of the present preregistered study was to examine whether student teachers’ expected future teaching-related emotions show a peak-end effect. Student teachers viewed fourteen common events that could part of a typical everyday routine of a teacher and rated their expected emotional pleasure and discomfort for each of the events. Afterwards, they were asked to rate their overall expected emotional pleasure and discomfort when looking at their future professional life as a whole. Results showed that expected pleasure was much larger than expected discomfort regarding both overall, peak, and average ratings. No peak-end effect was observed for overall expected discomfort which reflected the average expected discomfort across events. By contrast, overall expected pleasure was biased towards expected peak pleasure experiences. These findings indicate that student teachers judge their expected overall affect in a functional way: realistically when dealing with negative emotions but through rose-colored glasses when dealing with positive emotions.